ONLINE HEMODIAFILTRATION: CLINICAL RESULTS AND ECONOMIC EVALUATION - Y. L. Poz; A. G. Strokov; Y. V. Kopylova (Вестник трансплантологии и искусственных органов, 2014)
Second part of review summarizes legal and financial aspects of online hemodiafiltration and its influence on short-term and long-term treatment results. According to recently completed randomized clinical trials, high vo- lume online hemodiafiltration is able to improve patients' survival rate. The results mentioned in the review must overpower the inertia which obstructs a wide implementation of online hemodiafiltration into routine clinical practice.